2014
DOI: 10.1007/s00167-014-3369-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical reconstruction of posterolateral corner and combined injuries of the knee

Abstract: Case series with no comparative group, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…A recently published series by van der Wal et al of 16 patients who underwent the LaPrade two-tailed technique for lateral-sided reconstruction was prospectively reviewed. 28 At 2 to 5-year follow-up, varus laxity was significantly improved from pre-reconstruction value, 9.6 (6.6-17.1) to 6.3 degrees (0.3-16.1); however, varus laxity was not restored to the contralateral uninjured state. All clinical outcome scores demonstrated a statistically significant increase.…”
Section: Biomechanical and Clinical Resultsmentioning
confidence: 87%
“…A recently published series by van der Wal et al of 16 patients who underwent the LaPrade two-tailed technique for lateral-sided reconstruction was prospectively reviewed. 28 At 2 to 5-year follow-up, varus laxity was significantly improved from pre-reconstruction value, 9.6 (6.6-17.1) to 6.3 degrees (0.3-16.1); however, varus laxity was not restored to the contralateral uninjured state. All clinical outcome scores demonstrated a statistically significant increase.…”
Section: Biomechanical and Clinical Resultsmentioning
confidence: 87%
“…The mean IKDC score of 73.1 is slightly higher than the previous three reports evaluating this surgical technique despite including only patients with MKLIs. [17][18][19] This may be attributable to the relatively fewer female patients in this study (4/20, 20%), given that females have been shown to have lower IKDC scores following KD. 29 Alternatively, the difference may be related to the time interval from injury to surgery.…”
Section: Discussionmentioning
confidence: 87%
“…This technique has demonstrated satisfactory International Knee Documentation Committee (IKDC), Lysholm, and Cincinnati functional scores. [17][18][19] However, more than a third of patients (33-43%) in each of these previous cohorts had undergone isolated FCL/PLC reconstruction. Although injury to the PLC can occur in isolation, most PLC injuries present as a component of a multiligament knee injury (MKLI).…”
mentioning
confidence: 99%
“…The authors' experience and the peer-reviewed literature support two-tailed techniques in terms of providing the most consistent stability and anatomic restoration of the key structures. [1][2][3]9 However, there are deficiencies of the two-tailed techniques that ideally should be addressed. A recent prospective outcomes study by van der Wal et al-reporting on the use of the technique described by LaPrade et al-showed that varus stability was improved but not completely restored to match that in the contralateral, uninjured knee in patients at 5-year follow-up.…”
Section: Surgical Techniquementioning
confidence: 99%
“…A recent prospective outcomes study by van der Wal et al-reporting on the use of the technique described by LaPrade et al-showed that varus stability was improved but not completely restored to match that in the contralateral, uninjured knee in patients at 5-year follow-up. 1,9 In addition, the use of a screw and spiked washer for graft fixation can be associated with complications and morbidity. In the senior author's practice, approximately 25% of patients have undergone removal of the screw and washer due to pain and iliotibial band (IT) band irritation.…”
Section: Surgical Techniquementioning
confidence: 99%